BIOLOGI ULAT GRAYAK Spodoptera frugiperda J.E. Smith (Lepidoptera: Noctuidae) PADA TANAMAN JAGUNG - Fadel, Moh.; Anshary, Alam (Fakultas Pertanian, Universitas Tadulako, 2023)
The research objective was to investigate the biology of the armyworm pest (Spodoptera frugiperda). The study was conducted at the Plant Pests and Diseases Laboratory, Faculty of Agriculture, Tadulako University, spanning from February 2020 to April 2020. The findings revealed the duration of each life stage in the life cycle of S. frugiperda: the egg stage last for approximately 3 days, the first instar larvae stage range from 2 to 3 days, the second instar larvae stage range from 2 to 3 days, the third instar last for 3 to 4 days, the fourth instar larvae stage range from 2 to 4 days, the fifth instar larvae stage last for 2 to 3 days, and the sixth instar larvae stage persist for 3 days. The pupae stage lasts for 8 to 11 days, the male imago stage span 9 to 11 days, and the female imago stage range from 10 to 13 days. Overall, the total life cycle for males is approximately 36 to 42 days, while for females, it is around 37 to 45 days. Additionally, the female imago displays a pre-oviposition period lasting 3 to 4 days, followed by an oviposition period of 5 to 6 days, and finally, a post-oviposition period of 2 to 4 days. The research also revealed the production of 7 groups of eggs with a total of 815 eggs per group.